Kombinasi Pengukuran Radioaktivitas Batuan dan Geofisika dalam Menentukan Akuifer Airtanah Potensial di Desa Sumbermanjing Kulon, Pagak, Malang, Jawa Timur - Sukadana, I Gde; Indrastomo, Frederikus Dian (EKSPLORIUM, 2011)
The study area is an area with difficulties in fresh water supply. This study aimed to investigate geological characteristics, stratigraphical traps and sub surface geophysical characteristics to identify aquifer existance, depth and distribution. The purpose of this study is to determine the potencial location for groundwater drilling to fulfill the needs of fresh water in this area. Stages of activities include topography mapping, geological mapping, soil/rocks radioactivity measurements, geoelectric (resistivity) surveys and potential location determination analysis for drilling. The study area is an area with undulating terrain, litologically composed with sandstone unit and limestone unit. Radioctivity value of limestone ranged from 30c/s to 45c/s, carbonaceous sandstone ranged from 20c/s to 30c/s, and tuffaceous sandstone lower than 20c/s. Based from geoelectrical measurements analysis, lithologically this area devide into 4 rock layers, i.e. limestone (>100Wm), claystone (1Wm - 7 Wm), sandstone-1 (10Wm - 33Wm), and sandstone-2 (14Wm - 17 Wm). Integrated analysis resulted 2 potential location for drilling with coordinates for location 1 UTM 49M 664327mT, 9082526mU, 346 mdpl and location 2 UTM 49M 664333mT, 9082750mU, 349 mdpl.